Psychopathology : Contemporary Jungian Perspectives. - Samuels, Andrew (Library of analytical psychology., 1989)
The latest addition to the Library of Analytical Psychology is an outstanding collection of papers written by Jungian analysts from different schools of analytical psychology on various aspects of psychopathology. The subjects covered include depression, anorexia, schizoid personality, narcissistic personality disorder, mania, psychosis, paranoia, masochism, fetishism, transvestisism, perversion, marital dysfunction, survivor syndrome, and old age.The contributors, who include some of the most creative and distinguished clinicians in the Jungian world today, are: Gustav Dreifuss, Alan Edwards,